Respuesta :

Answer:

[tex](x+\frac{b}{2a})^2+(\frac{4ac}{4a^2}-\frac{b^2}{4a^2})=0[/tex]

[tex](x+\frac{b}{2a})^2=\frac{b^2-4ac}{4a^2}[/tex]

[tex]x=\frac{-b}{2a} \pm \frac{\sqrt{b^2-4ac}}{2a}[/tex]

Step-by-step explanation:

[tex]x^2+\frac{b}{a}x+\frac{c}{a}=0[/tex]

They wanted to complete the square so they took the thing in front of x and divided by 2 then squared.  Whatever you add in, you must take out.

[tex]x^2+\frac{b}{a}x+(\frac{b}{2a})^2+\frac{c}{a}-(\frac{b}{2a})^2=0[/tex]

Now we are read to write that one part (the first three terms together) as a square:

[tex](x+\frac{b}{2a})^2+\frac{c}{a}-(\frac{b}{2a})^2=0[/tex]

I don't see this but what happens if we find a common denominator for those 2 terms after the square.  (b/2a)^2=b^2/4a^2 so we need to multiply that one fraction by 4a/4a.

[tex](x+\frac{b}{2a})^2+\frac{4ac}{4a^2}-\frac{b^2}{4a^2}=0[/tex]

They put it in ( )

[tex](x+\frac{b}{2a})^2+(\frac{4ac}{4a^2}-\frac{b^2}{4a^2})=0[/tex]

I'm going to go ahead and combine those fractions now:

[tex](x+\frac{b}{2a})^2+(\frac{-b^2+4ac}{4a^2})=0[/tex]

I'm going to factor out a -1 in the second term ( the one in the second ( ) ):

[tex](x+\frac{b}{2a})^2-(\frac{b^2-4ac}{4a^2})=0[/tex]

Now I'm going to add (b^2-4ac)/(4a^2) on both sides:

[tex](x+\frac{b}{2a})^2=\frac{b^2-4ac}{4a^2}[/tex]

I'm going to square root both sides to rid of the square on the x+b/(2a) part:

[tex]x+\frac{b}{2a}=\pm \sqrt{\frac{b^2-4ac}{4a^2}}[/tex]

[tex]x+\frac{b}{2a}=\pm \frac{\sqrt{b^2-4ac}}{2a}[/tex]

Now subtract b/(2a) on both sides:

[tex]x=\frac{-b}{2a} \pm \frac{\sqrt{b^2-4ac}}{2a}[/tex]

Combine the fractions (they have the same denominator):

[tex]x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]

ACCESS MORE